Invertebrates (Echinodermata, Brachiopoda, Bryozoa, Cnidaria, Porifera) from the Carboniferous of Sierra Santa Teresa, Sonora, Mexico: Paleoecological and paleogeographic considerations - Cuadros-Mendoza, Iván Manuel; Buitrón-Sánchez, Blanca Estela; Cuen-Romero, Francisco Javier; Torres-Martínez, Miguel Ángel; Caballero-Ochoa, Andrea Alejandra (Revista de Biología Tropical, 2024)
Introduction: The Sierra Santa Teresa is located 20 km southeast of Hermosillo in the central region of Sonora state, Mexico. The sedimentary strata mainly correspond to limestone, mudstone, wackestone and packstone texture, from the upper Paleozoic. The biota is represented by crinoids of the morphospecies Baryschyr anosus, Cyclocaudex insaturatus, Floricyclus angustimargo, Cyclocion distictus, Lamprosterigma erathense, Preptopremnum rugosum in association with algae, fusulinid foraminifera, coralline sponges (Chaetetes sp.), solitary corals (Lophophyllidium sp., Fomichevella sp.), fenestellid bryozoans (Archimedes stoyanowi), and brachiopods (Antiquatonia sp.). Objective: The principal aim of this study is to analyze the biotic composition in the Sierra Santa Teresa and its paleoecological and paleogeographical considerations. Methods: In this study we synthetize information about the principal taxa collected in outcrops of the Carboniferous of the Sierra, Santa Teresa. Results: The distribution of the biota, and particularly the crinoid morphospecies, allowed paleobiogeographical correlations to be made with other Mississippian-Pennsylvanian localities of Mexico and different regions of the United States of America in Texas, Colorado, Illinois and Oklahoma, which were located in the southwestern of the North American Craton. Conclusions: It is considered that the paleoenvironment inferred based on the paleontological records of the Sierra Santa Teresa were shallow seas that allowed the development of communities of crinoids, as well as other invertebrates such as coralline sponges, solitary corals, fenestellid bryozoans and brachiopods, with a range stratigraphic from the Middle-Upper Mississippian (Chesterian) to the Middle Pennsylvanian (Desmoinesian).